LINGUISTICS AND DIDACTICAL TESTING AS A MEANS OF LEXICAL COMPETENCE IMPROVEMENT OF STUDENTS - Larina, Tetyana V. (Educological discourse, 2015)
The article deals with language testing in terms of language competence development. The standard approach to test formation is highlighted. The emphasis is put on the set of linguistics and didactical tests to encourage the development of language skills in general and to acquaint students with international testing systems. «Use of English» tests, focused on preventing students from making common mistakes, are given for individual studying. The structure as well as the components of the supplements are analyzed.